Efektifitas Penerapan Konsep Smart City Ditinjau Dari Aspek Indeks Pembangunan Manusia Di Kota Semarang - Eko Muliawan Satrio; Agus Rochani (UNISSULA Semarang, 2019)
ABSTRACTSmart people are the basis of the realization of Smart Cities. This relates to the formation of smart cities, must have intelligent human resources and supported by policies and infrastructure of mobility, governance, economy and environment that are also smart to produce the quality of life as intelligent as desired. Semarang City Government, has been implementing the concept of smart cities since 2013. This travel program is very dynamic in the field. For this reason, it is necessary to consider the effectiveness of the application of the smart city concept by the Semarang City Government to the community. The assessment carried out is by calculating the Human Development Index (HDI) or can also be called the Human Development Index (HDI). Through this evaluation, making information about the application of the Smart Cities concept specifically reviews aspects of human development. (